Salinomycin and Other Ionophores as a New Class of Antimalarial Drugs with Transmission-Blocking Activity - D'Alessandro, Sarah (Antimicrob Agents Chemother, 2015)
The drug target profile proposed by the Medicines for Malaria Venture for a malaria elimination/eradication policy focuses on molecules active on both asexual and sexual stages of Plasmodium, thus with both curative and transmission-blocking activities. The aim of the present work was to investigate whether the class of monovalent ionophores, which includes drugs used in veterinary medicine and that were recently proposed as human anticancer agents, meets these requirements. The activity of salinomycin, monensin, and nigericin on Plasmodium falciparum asexual and sexual erythrocytic stages and on the development of the Plasmodium berghei and P. falciparum mosquito stages is reported here. Gametocytogenesis of the P. falciparum strain 3D7 was induced in vitro, and gametocytes at stage II and III or stage IV and V of development were treated for different lengths of time with the ionophores and their viability measured with the parasite lactate dehydrogenase (pLDH) assay. The monovalent ionophores efficiently killed both asexual parasites and gametocytes with a nanomolar 50% inhibitory concentration (IC(50)). Salinomycin showed a fast speed of kill compared to that of standard drugs, and the potency was higher on stage IV and V than on stage II and III gametocytes. The ionophores inhibited ookinete development and subsequent oocyst formation in the mosquito midgut, confirming their transmission-blocking activity. Potential toxicity due to hemolysis was excluded, since only infected and not normal erythrocytes were damaged by ionophores. Our data strongly support the downstream exploration of monovalent ionophores for repositioning as new antimalarial and transmission-blocking leads.